2020
DOI: 10.3390/app10072356
|View full text |Cite
|
Sign up to set email alerts
|

Electromyography Analysis of Muscle Activation During Stand-Up Paddle Boarding: A Comparison of Paddling in Kneeling and Standing Positions

Abstract: Background: This study aimed to understand individual muscle use in different paddling postures in stand-up paddle boarding (SUP). Methods: Sixteen college students were recruited in this study. Surface electromyography of 16 muscles on the dominant side was recorded. Results: In the time series, the biceps muscle exhibited a continuous activation pattern in the pull phase when kneeling, whereas when standing, the muscle contracted considerably in the exit and recovery phases, implying that it plays different … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
13
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(14 citation statements)
references
References 14 publications
0
13
1
Order By: Relevance
“…A comparison of paddle stroke mechanics between experienced and inexperienced SUP participants by Schram et al [14] revealed that inexperienced participants showed higher overall shoulder action and less hip range of motion than experienced participants. Muscle activation during paddling appears to primarily involve the upper extremities, trunk, hip stabilizers, and knees [9,17]. During SUP in an ergometer and at sea, it was demonstrated that muscle activation during the water-based test started sooner and was maintained longer than that during the ergometer test [17].…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…A comparison of paddle stroke mechanics between experienced and inexperienced SUP participants by Schram et al [14] revealed that inexperienced participants showed higher overall shoulder action and less hip range of motion than experienced participants. Muscle activation during paddling appears to primarily involve the upper extremities, trunk, hip stabilizers, and knees [9,17]. During SUP in an ergometer and at sea, it was demonstrated that muscle activation during the water-based test started sooner and was maintained longer than that during the ergometer test [17].…”
Section: Introductionmentioning
confidence: 99%
“…It has become a popular and accessible activity with numerous benefits, including improvements in body mass index, aerobic and anaerobic fitness, and multidirectional trunk strength, as well as applications for rehabilitation and fall prevention [2][3][4][5][6]. Despite its growing popularity, research on SUP remains limited, with few studies investigating its physiology [7,8], biomechanics [9,10], epidemiology [11,12], and psychology [6] in both recreational and competitive participants [13][14][15].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations